2013
DOI: 10.1186/1477-7525-11-146
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes to aging mediate the relationship between older peoples’ subjective health and quality of life in 20 countries

Abstract: BackgroundWith ever-increasing life expectancy globally, it is imperative to build knowledge of how older peoples’ views of their own aging, considering their health-related circumstances, affect quality of life for practitioners and policy-makers alike. Based on our literature review, we wanted to determine whether older adults’ attitudes toward their own aging would partly mediate the effect of their health satisfaction ratings upon their quality of life. Furthermore, would these attitudes mediate the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
90
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(110 citation statements)
references
References 56 publications
16
90
0
4
Order By: Relevance
“…These scores were 0.807, 0.809, and 0.738, respectively. Low et al () reported the internal consistency reliability for the scale was 0.86 for the entire instrument (0.81 for physical change and 0.74 and 0.81 for psychological growth and psychological loss, respectively). Eser et al () assessed the validity and reliability of this instrument in Turkey.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These scores were 0.807, 0.809, and 0.738, respectively. Low et al () reported the internal consistency reliability for the scale was 0.86 for the entire instrument (0.81 for physical change and 0.74 and 0.81 for psychological growth and psychological loss, respectively). Eser et al () assessed the validity and reliability of this instrument in Turkey.…”
Section: Methodsmentioning
confidence: 99%
“…Low, Molzahn, and Schopflocher () defined attitudes as stable, integrative judgments that summarize the thoughts, feelings, and memories of people regarding objects or situations. Attitudes are derived from direct experience or from observation.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, older people's self-perceptions of health can be greatly affected by other factors, including their attitudes toward their own ageing. 31 Nor do these approaches take account of the differing environments or differential access to services between countries that might mitigate the effects on functioning of different disorders.…”
Section: The Epidemiology Of Population Ageingmentioning
confidence: 99%
“…Attitudes measured with the AAQ have been found to be associated with a range of health and well-being benefits among midlife and older adults (Bryant et al, 2012;Low, Molzahn, & Schopflocher, 2013). The relationships between attitudes and health outcomes, however, are likely to be bi-directional, and, to date, only one study has identified psychological factors that might explain why some people hold more positive attitudes to ageing than others, based on scores on the AAQ ).…”
Section: Introductionmentioning
confidence: 94%